1992
DOI: 10.1515/zna-1992-1002
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization of Diphenyl Polyenes. Part II. Fluorescence Properties of 1,8-Diphenyl-1,3>5,7-octatetraene in Poly (vinyl alcohol) Film

Abstract: The effect of temperature on the fluorescence properties of 1,8-diphenyl-1,3,5,7-octatetraene (DPO) in polyvinyl alcohol) film (PVA) was investigated in the range from 295 to 428 K. Upon heating above 353 K, the quantum yield of D PO increases rapidly. This effect is irreversible, similarly as the optical density in the long wavelength absorption band (320-440 nm). It has its origin in the cis-trans conversion of DPO molecules in PVA film at high temperatures. The behaviour of the fluorescence anisotropy in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1992
1992
1995
1995

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…As already shown in [16], the fluorescence quantum yield, grows dramatically upon heating the DPO sample in PVA to above 358 K. Table 1 summarizes the quantum yield values determined for DPO in different polymers either non-heated or heated to 423 K. In the case of DPO in PVCh, PVF and EtA (nonheated samples), <P F amounts to about 0.22, being very low for the non-heated DPO sample in PVA (0.03) and even lower than for DPO in cyclohexane and methanol. The values of for DPO in PVCh, PVF and EtA heated to 423 K are almost the same as for the nonheated samples, while for the heated DPO in PVA a strong increase in <P F is observed, even to 0.32, which is markedly higher than the quantum yield in the remaining polymers.…”
Section: Fluorescence Quantum Yields and Lifetimessupporting
confidence: 72%
See 2 more Smart Citations
“…As already shown in [16], the fluorescence quantum yield, grows dramatically upon heating the DPO sample in PVA to above 358 K. Table 1 summarizes the quantum yield values determined for DPO in different polymers either non-heated or heated to 423 K. In the case of DPO in PVCh, PVF and EtA (nonheated samples), <P F amounts to about 0.22, being very low for the non-heated DPO sample in PVA (0.03) and even lower than for DPO in cyclohexane and methanol. The values of for DPO in PVCh, PVF and EtA heated to 423 K are almost the same as for the nonheated samples, while for the heated DPO in PVA a strong increase in <P F is observed, even to 0.32, which is markedly higher than the quantum yield in the remaining polymers.…”
Section: Fluorescence Quantum Yields and Lifetimessupporting
confidence: 72%
“…The methods of measuring the absorption and fluorescence spectra, and the quantum yields and emission anisotropies were described in [15][16][17]. Fluorescence decays were measured on a K 2 multifrequency cross-correlation phase and modulation fluorometer at the Biochemistry Department of the University of Ancona, Italy.…”
Section: Wavelength [Nm]mentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter cases, i.e. for l,6-diphenyl-l,3,5-hexatriene (DPH) and 1,8-diphenyl-l,3,5,7-octatriene (DPO) in PVA, an unusual behaviour of absorbance and quantum yield was ob served above the glass transition temperature (Tg = 358 K), which enabled the conclusion that above this temperature thermal cis-trans isomerization occurs in the ground state [1,3,5,6]. In addition, based on quantum yield and mean fluorescence lifetime decay measurements it was found that for the three polyenes fluorescence emission is due to trans-trans and cistrans conformers.…”
Section: Introductionmentioning
confidence: 99%
“…In previous papers [1][2][3][4][5][6][7][8] the effect of temperature and light on the photophysical and photochemical properties of linear polyenes, Ph-(CH = CH)"-Ph, n = 2, 3, 4, in poly(vinyl alcohol) (PVA) films were investigated. The behaviour of the polyene with n = 2, i.e.…”
Section: Introductionmentioning
confidence: 99%